Galatians 6:17 and its Reception History: Assessing the Echoes - Muir, Steven (Vox Patrum, 2024)
This preface engages with the concept of echo as a creative way of generating ideas on how to assess issues in the reception history of a scripture text – here, Galatians 6:17.